KAJIAN FIKIH KONTEMPORER: SEBUAH REKONSTRUKSI AWAL - Aibak, Kutbuddin (Ahkam: Jurnal Hukum Islam, 2014)
Principally, any knowledge which is systematically codified andcommunicated either in oral and written form has philosophicalbasis. The basic assumption of a scientist which is followedby scientific steps of research such as using correct approach,employing theoretical framework, checking appropriatevalidity of information, finding the relationship between subjectand object is central to the structure of knowledge includingscience, humanity, social, and religion. As such, knowledge hascertain structure by which it opens to further investigation anddevelopment.Kata kunci: Kajian Fikih Kontemporer, Metode, Pendekatan